Magnetic Observations at International Polar Year Stations in Canada - Newitt, L.R.; Dawson, E. (ARCTIC, 1984)
During the First International Polar Year (1982-83) magnetic observatories were established in northern Canada at Fort Rae, Fort Conger, and Clearwater Fiord. Repeat magnetic observations made during the centenary of the First Polar Year enable a determination of the secular variation at each of these locations. During the last 100 years the declination has increased easterly by over 20 degrees at Fort Conger and at Clearwater Fiord; however, it has decreased by only 9 degrees at Fort Rae. The total intensity has decreased by over 1900 nT at Fort Rae, but at Clearwater Fiord and at Fort Conger the decrease has been about 1500 nT and 1000 nT respectively. This implies that the decrease in the non-dipole field evident over most of North America in recent times has not been as great in the high Arctic.Key words: Polar Year, Fort Conger, Fort Rae, Clearwater Fiord, Kingua Fiord, secular variation, magnetic field Mots clés: Année polaire, Fort Conger, Fort Rae, fjord Clearwater, fjord Kingua, variation séculaire, champ magnétique